The Implementation of Islamic Religious Education Values through the Muhadhoroh Extracurricular Activity at Pondok Modern Darussalam Gontor 7 - Muhammad Al Imron; Maylia Khairunnisa Baher; Icha Mufassiroh Asy Syauqi; Agus Pahrudin; Achi Rinaldi; Ali Murtadho (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to analyze the implementation of Islamic Religious Education (PAI) values through the Muhadhoroh extracurricular at Pondok Modern Darussalam Gontor 7. The research method uses a qualitative approach with data collection techniques through participatory observation, in-depth interviews with caregivers, teachers, and students, as well as documentation studies. The research results show that Muhadhoroh is effective as a medium for instilling PAI values such as honesty, responsibility, discipline, and ukhuwah islamiyah through three main stages: material preparation, delivery practice, and continuous evaluation. The learning system integrated with the pesantren curriculum and a phased approach according to the students' abilities has been a supporting factor for success. This extracurricular activity not only develops communication skills but also shapes the character of students to be ready to become preachers in society. The research findings recommend Muhadhoroh as an ideal model of extracurricular activities based on Islamic Education values that can be adopted by other educational institutions.